2022
DOI: 10.1186/s12864-021-08222-9
|View full text |Cite
|
Sign up to set email alerts
|

Amphioxus muscle transcriptomes reveal vertebrate-like myoblast fusion genes and a highly conserved role of insulin signalling in the metabolism of muscle

Abstract: Background The formation and functioning of muscles are fundamental aspects of animal biology, and the evolution of ‘muscle genes’ is central to our understanding of this tissue. Feeding-fasting-refeeding experiments have been widely used to assess muscle cellular and metabolic responses to nutrition. Though these studies have focused on vertebrate models and only a few invertebrate systems, they have found similar processes are involved in muscle degradation and maintenance. Motivation for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 176 publications
(161 reference statements)
1
0
0
Order By: Relevance
“…By this criterion, MymX ortholog was not found from the tunicate species. Consistently, a recent study reported the absence of both MymX and MymK genes in amphioxus ( 46 ).…”
Section: Methodssupporting
confidence: 83%
“…By this criterion, MymX ortholog was not found from the tunicate species. Consistently, a recent study reported the absence of both MymX and MymK genes in amphioxus ( 46 ).…”
Section: Methodssupporting
confidence: 83%